2000
DOI: 10.1177/026988110001400403
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine pharmacokinetics and pharmacodynamics studied with CYP1A2-null mice

Abstract: The aim of this study was to use the CYP1A2-null mouse to investigate the in-vivo contribution of CYP1A2 to clozapine pharmacokinetics and pharmacodynamics. An intraperitoneal injection of 10 mg/kg clozapine was administered to four male CYP1A2 -/- mice and four male wild-type mice. Clozapine, desmethylclozapine, and clozapine N-oxide concentrations in sequential tail blood samples were measured by HPLC with UV detection. Behavioural parameters were recorded at each time point. The area under the curve (AUC) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 42 publications
1
22
0
3
Order By: Relevance
“…A washout period of 24 h or more was allowed between two consecutive treatments. The washout periods were more than 10 times the half-lives of clozapine (110 min 20 ) and the 5-HT2A antagonist MDL100907 (71 min 21 ) and exceeded the duration of previously reported EEG effects (5-HT2BC;SB206553: 3 h 14 ) by eightfold. The animals were treated in matched pairs of the same sex and body weight and opposite genotype.…”
Section: Experimental Pharmacological Protocolmentioning
confidence: 63%
“…A washout period of 24 h or more was allowed between two consecutive treatments. The washout periods were more than 10 times the half-lives of clozapine (110 min 20 ) and the 5-HT2A antagonist MDL100907 (71 min 21 ) and exceeded the duration of previously reported EEG effects (5-HT2BC;SB206553: 3 h 14 ) by eightfold. The animals were treated in matched pairs of the same sex and body weight and opposite genotype.…”
Section: Experimental Pharmacological Protocolmentioning
confidence: 63%
“…Clozapine is also subject to considerable metabolism by the cytochrome P450 (CYP) enzyme system (Aitchison et al, 2000). There are numerous variants of the genes encoding the CYP enzyme family within the general population, resulting in complex individual genetic profiles and a variable response to drugs metabolised by these enzymes (Ma et al, 2004).…”
Section: Managing Clozapine-resistant Patientsmentioning
confidence: 99%
“…From a pharmacokinetic point of view, it has been shown that CYP1A2 is the major determinant of clozapine clearance [4] (though CYP2C19, 2D6, 3A4, and 2C9 are also involved), and that there is wide interindividual variation in its activity [5]. Several polymorphisms of the CYP1A2 gene have been identified; some of them are significant and others are not.…”
Section: Clozapinementioning
confidence: 99%